A demand–capacity mismatch between rehabilitation need and service provision as a result of the COVID-19 pandemic? Early clinical observations from a large teaching hospital in London. (December 2021) - Tahtis, Vassilios; Wilson, Nicky; Northfield, Frankie; Cook, Donna; Gregory, Kate; Reilly, Charles C.
Abstract: In this short report the authors characterise inpatient bed occupancy and predicted rehabilitation need of patients cared for in two acute hospitals of a large London NHS Trust during the first wave of the COVID-19 pandemic, including 394 people with confirmed COVID-19. Data were captured on a single day (17 th April 2020) from the two Trust hospitals to inform discharge planning in line with national COVID-19 Hospital Discharge Service policy guidance. Our data suggests that the proportion of COVID-19 patients predicted to require rehabilitation upon hospital discharge may be greater than the estimates described in the national COVID-19 Hospital Discharge Service policy guidance; posing the question is there a demand–capacity mismatch between rehabilitation need and service provision as a result of the COVID-19 pandemic?